RIVIEW SKEMA ACFTA TERHADAP EKSPOR INDONESIA KE TIONGKOK, HONGKONG DAN ASEAN - Made Adnyana (Populis : Jurnal Sosial dan Humaniora, 2016)
In addition to the free trade accord of Bali II, Indonesia has also agreed to implement ACFTA with RRChina and Hongkong. Four schemes agreed up on are Early Harvest Program (EHP), Normal Track (NT) Sensitive Track (ST) and Highly Sensitive Track (HST). The  method used in the study is applying  New Trade Theory model, i.e. involving Comparative Advantage determinants, along with regression analysis. The study  focuses on  data on export volume of  1996 up to  2013 on three-monhly basis. The finding of the study is that certain commodities have gained promising export in 2010; steady export growth has been experienced by two commodities numbered as 87 and 27 at the schemes.   The number 26 commodity at the scheme experienced the decline. Keywords: ACFTA schemes, exsport from Indonesia, RR China, Hongkong